Challenges for Life Cycle Assessment Of Palm Oil Production System - Heinz Stichnothe; Cécile Bessou (Indonesian Life Cycle Assessment Network (ILCAN), 2017)
Growing demand for palm oil is driven by increasing human population, income growth as well as biodiesel stimulation programs. Covering an area of over ten million ha in Indonesia, palm oil production is also one of the most important sources of crop residues while processing generates large amounts of wastewater. Cultivation and processing of this crop are considered as potentially large sources of emissions. Improving environmental impacts of the palm oil production can help to reduce existing emissions while increasing yield and generating surplus energy and farm income. However, area expansion for oil palm plantation is perceived as closely linked to illegal logging, deforestation and diminishing biodiversity. Apart from ensuring sustainable land use change, the use of residues is the most important criterion in ensuring sustainable palm oil. It is important to note that there are trade-offs (e.g. between maximizing bio energy production, reducing environmental impacts other than greenhouse gases (GHG), and sustaining soil fertility). Nitrogen (N) losses in palm oil production systems are a major environmental and economic issue. Unfortunately, there is little comprehensive knowledge on how to calculate N-budgets in oil palm plantation in order to optimize fertilization, taking into account N-leaching and N-gaseous emissions. Land use, soil-carbon, N-emissions and biodiversity are key aspects of life cycle assessment (LCA) of palm oil production systems and they pose a number of methodological questions.